DHAWABITH INKAR AL . MUNKARDirasah Nadlariyah'Ta'shiliyah Fi Qaidah La DhararaWa La Dhirara Wa Fiqh lnkar Al-Munkar - AZIZ, TAMIM (2012)
The guidelines of the alteration of evil, a theorical study based on the rule of Islamic Jurisprudence, "there is no harm nor inflicting harmful". This is a Thesis submitted for the Master Programme of Islamic Thought and Islamic Jurisprudence Department, at the University of Muhammadiyah Surakarta. Prepared by: Tamim Aziz, supervised by Dr. Muhammad Muinudinillah Basri. and Dr. Mochammad Ichsan. In 2012 AD -1433 H. The notion of this qualitative and librarical research is basically urged by the realitiy of da'wah which has been in need of certain guidelines dealing with the alteration of evil under the rule of Islamic Juris prudence, "there is no harm nor inflicting harmful ." Among the reasons of the critical need of this study is the emergence of the undesirable phenomenon in the arena of da'wah, that is hasty enthusiasm in the way of the alteration of evil; neglecting the negative results of the actions and and losses. The study then raises two important questions as follows: (1) What does the rule "there is no harm nor inflicting harmful" mean? And What does the guidelines of the alteration of evil mean as well as their relationship between each other? (2) What kinds of guidelines could be derived from the rule "there is no harm nor inflicting harmful" for the purpose of the alteration of evil? After intensive studies in each of the two fields of the Islamic jurisprudences, pertaining to the rule "there is no harm nor inflicting harmful", and making the comparison between the two subjects as well as looking at their relationships between each other, finally the study came up with a set of the rules related to the alteration of the evil. These rules are: firstly - the general rule in the alteration of evil, which is keeping and making the interests come true, and refuting and neglecting the harms. Secondly - the rules that are derived from the rule of keeping and making the interests come true and refuting and neglecting the harms lead to some important results: (1) the correct perception of the concept of evil, and the Islamic jurisprudence related to the alteration of evil. (2) identification and verification before proceeding the alteration of evil. (3) starting from the worst of the evil. (4) calling to goodness and preventing from badness before denying and alteration of evil (5) choosing lesser of two evils. (6) the alteration of evil should not entail greater evil . These rules presumably could light up the path of da'i in the field of da'wah and direct their genuine concern on the alteration of evil toward the correct way for the sake of refuting the harm and keeping the interest.